2014
DOI: 10.1007/s12098-014-1461-0
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Hemophagocytic Lymphohistiocytosis; Efficacy of Intravenous Immunoglobulin Therapy

Abstract: IVIG and HLH-2004 protocol may be equally effective in the management of HLH. IVIG may be a preferable initial regimen, to avoid the risk of secondary malignancy associated with etoposide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…The study used a preselection of all cases of hyperferritinemia, and control groups did not represent all patients admitted to the MICU. However, previous retrospective data showed that the prevalence of hyperferritinemia in HLH is >90 % (and approaches 100 %) [32,36,37]. Any conclusions regarding relative sensitivity and specificity must be drawn against this cohort selection.…”
Section: Limitationsmentioning
confidence: 98%
“…The study used a preselection of all cases of hyperferritinemia, and control groups did not represent all patients admitted to the MICU. However, previous retrospective data showed that the prevalence of hyperferritinemia in HLH is >90 % (and approaches 100 %) [32,36,37]. Any conclusions regarding relative sensitivity and specificity must be drawn against this cohort selection.…”
Section: Limitationsmentioning
confidence: 98%
“…The principal goal of therapy in hyperferritinemic sydromes is to suppress the life-threatening inflammatory process. Hyperferritinemic syndromes (acquired HLH/sepsis/ MODS/MAS) have been successfully treated with intravenous immunoglobulin (IVIg), methylprednisolone, plasma exchange and anakinra [51,[71][72][73]. Indeed, these therapies can be effective modalities, individually or in combination.…”
Section: Managing Cytokine Production And/or Eliminationmentioning
confidence: 99%
“…IVIg is indicated at least theoretically in the view of many mechanism of actions: Fc-receptor blockade, activation of the inhibitory Fcg-receptor IIB, inhibition of complement activation, down regulation of T/B-cell functions, anti-idiotypic suppression, neutralization of superantigens or infectious agents, neutralization of cytokines, enhanced clearance of pathogenic antibodies [77][78][79][80]. The administration of IVIg alone or in combination with other treatment modalities has been described in hyperferritinemic syndromes [71,72]. Variable efficacy is demonstrated, which is not astonishing give the heterogeneity of hyperferritinemic syndromes, the different IVIg preparations on the market, the inherent batch variability, the different dosing schedules, and variability of administration time points used.…”
Section: Ivigmentioning
confidence: 99%
See 1 more Smart Citation
“…Y lleva 3 años en remisión, lo que contrasta claramente el pronóstico descrito de SHF de sobrevida media de 2,1 meses en general y 1,4 meses en SHF asociado a neoplasias 19 . Existe alguna evidencia que la administración de IgIV más dexametasona es similar en respuesta al clásico protocolo HLH04 20 .…”
Section: Discussionunclassified